Analysis of Nationalism in Kurikulum Merdeka - Gupi Rohman Nurmansyah (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2023)
Nationalism is related to problems related to many people in a nation and country, such as corruption, radicalism, discrimination, and racism in culture. The concept of nationalism, according to experts from different countries, is almost entirely the same, as differences will not make a problem. Especially in Indonesia, the concept of nationalism has a critical position, even entering the realm of education. The Kurikulum Merdeka emphasizes Profil Pelajar Pancasila, who follows all the precepts in their design on the competence of graduates, but whether the five precepts are already in the mapping of the Kurikulum Merdeka needs to be carried out in-depth analysis. This research uses a qualitative approach to the literature study, which analyzes the Kurikulum Merdeka on Profil Pelajar Pancasila. The result is that the third precept, namely